EDUKASI KEWIRAUSAHAAN UNTUK MEMPERSIAPKAN CALON WIRAUSAHAWAN MUDA - Sherly Rosalina Tanoto; Roy Setiawan (Bajang Institute, 2024)
Entrepreneurship is crucial in driving economic growth and fostering innovation across various sectors. Through entrepreneurship education, young aspiring entrepreneurs gain a deep understanding of fundamental concepts, relevant technical skills, and the ability to spot opportunities while tackling challenges. This kind of education nurtures a creative and innovative mindset and helps develop resilience, preparing students to face risks and setbacks as part of their learning journey. By building extensive networks and gaining practical insights from real-world experiences, entrepreneurship education is a strong foundation for equipping the younger generation with the competence and confidence needed in the business landscape. Moreover, entrepreneurship education encourages these future entrepreneurs to strategically develop their business ideas. They learn to conduct thorough research, validate their concepts, and create detailed plans, all aimed at crafting solutions that meet market needs and positively impact society. Throughout this process, mastering technology, financial management, and interpersonal skills become essential for success, and these abilities should be continually refined. With a clear vision, dedication, and a passion for lifelong learning, young entrepreneurs can achieve personal success while contributing to sustainable economic and social development